Efektivitas Latihan Aerobic dan Isometric Berbasis Home-Based Exercise pada Pasien Congestive Heart Failure - Amalia Fardiana; Faizah Maulidiyah; Fransisco Godinho (Journal of Telenursing (JOTING), 2022)
This study aims to systematically review several kinds of literature that discuss the impact of training or physical activity of patients with Congestive Heart Failure (CHF) in lowering blood pressure in hypertensive patients. The method used is a systematic review by studying journal literature on the Scopus, CINAHL, Pubmed, ScienceDirect and SAGE Journals databases. The results showed that exercise could be done at home by the patient independently to support pharmacological treatment therapy in the cardiovascular system. The therapy can change the patient's behavior from maladaptive to adaptive. Treatment modalities can be given to patients with cardiovascular disorders: hypertension, namely cardiac exercise because cardiac exercise is an easy, light activity, can be done continuously and reduces the effects of pharmacological use. In conclusion, cardiovascular modality therapy is a home-based exercise program that can be given to patients with heart and blood flow disorders. Therapy that is run regularly can affect lowering blood pressure. Keywords: Aerobic, Hypertension, Exercise Program, Blood Pressure, Therapy